2016
DOI: 10.7181/acfs.2016.17.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Infraorbital Rim contour Using Medpor

Abstract: BackgroundAsymmetry of the infraorbital rim can be caused by trauma, congenital or acquired disease, or insufficient reduction during a previous operation. Such asymmetry needs to be corrected because the shape of the infraorbital rim or midfacial skeleton defines the overall midfacial contour.MethodsThe study included 5 cases of retruded infraorbital rim. All of the patient underwent restoration of the deficient volume using polyethylene implants between June 2005 and June 2011. The infraorbital rim was acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…(really high-thickness porous polyethylene) is a non-resorbable, and uneasy moulded polymer that has been in many cases utilized in the minimal floor of orbit deserts (23). This type of material has a smooth external surface and is incredibly biocompatible because the holes grant the improvement of veins and connective tissue (24). Medpor showed that titanium facial reconstructions got autologous bone tissue, yet illness rates were lower (7).…”
Section: Medpormentioning
confidence: 99%
“…(really high-thickness porous polyethylene) is a non-resorbable, and uneasy moulded polymer that has been in many cases utilized in the minimal floor of orbit deserts (23). This type of material has a smooth external surface and is incredibly biocompatible because the holes grant the improvement of veins and connective tissue (24). Medpor showed that titanium facial reconstructions got autologous bone tissue, yet illness rates were lower (7).…”
Section: Medpormentioning
confidence: 99%
“…Medpor (ultra-high-density porous polyethylene) is a non-resorbable, easy-to-shape polymer that has been frequently used in small orbital floor defects [ 56 ]. This material has a smooth surface and very good biocompatibility because the pores allow the formation of connective tissue and blood vessels [ 57 ]. The results obtained with Medpor were similar to those obtained with autologous bone tissue, but infection rates were lower [ 28 ].…”
Section: Biomaterials For Reconstructionmentioning
confidence: 99%
“…F acial bone fractures are common medical conditions widely discussed in plastic surgery. [1][2][3][4][5][6]7 When this type of facial bone fracture is associated with a temporoparietal bone fracture, the fracture extends to involve the bones in the temporal and parietal regions of the skull. The temporal bone forms the lower lateral sides of the skull, and the parietal bone forms the upper sides.…”
mentioning
confidence: 99%